Management of Alopecia and Onychomycosis in a Lupus Patient - Muzayyana Sakiinah; Awalia; Willy Sandhika; Stefanus Gunawan Kandinata; Katsuya Suzuki (Biomolecular and Health Science Journal)
The array of potential differential diagnoses of cutaneous lupus erythematosus (CLE) is extensive. Exclusion of infection is paramount, given the patient’s immunodeficient state. We report the case of a 33-year-old female patient who presented with pruritic erythematous papules across her upper extremities, originally presumed to be a drug eruption. Cutaneous xerosis and desquamation involving the hands were also noted, concomitant with diffuse hair loss and onychodystrophy. Potassium hydroxide and culture analysis from nail scrapings aligned with onychomycosis. Concurrently, histopathological assessment of the skin biopsy illustrated subacute CLE. Following the completion of the antifungal, mycophenolate mofetil was initiated, owing to suboptimal outcomes observed with the previous treatment modalities. The resolution of scaling on the scalp was concomitant with the emergence of new hair growth. Alopecia in lupus erythematosus patients mandates a thorough examination, owing to the extensive spectrum of its potential causes. Involvement of the nails mandates a rigorous exclusion of infections.